Review on Non Uniform Rational B-Spline (NURBS)Concept and Optimization - Munira, Ali; Nur Najmiyah, Jaafar; Fazilah, Abdul Aziz; Nooraizedfiza, Zainon (Trans Tech Publications, Switzerland, 2014)
This paper is to provide literature review of the Non Uniform Rational B-Spline (NURBS) formulation in the curve and surface construction.